2006
DOI: 10.1093/ps/85.12.2112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Semiochemical Analogue on Growing Performances and Meat Quality of Broilers

Abstract: Stress in broilers may have severe consequences on the final product quality. A synthetic analogue of uropygial secretion of mother hens was isolated from poultry. This mother hen uropygial secretion analogue (MHUSA) was tested in farm conditions on broilers during 12 wk. The purpose of this trial was to estimate the influence of MHUSA on growing performances, meat characteristics after processing, and stress indicators of broilers. After the 80-d period, birds under treatment were heavier at 3 different weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
4
11
1
Order By: Relevance
“…Previous studies using MHUSA in broilers showed that birds under this semiochemical had greater LW compared with control (Madec et al, 2005(Madec et al, , 2006(Madec et al, , 2008. The current study results are similar for LW, but the results did not support the hypothesis that CI would be improved for broilers exposed to MHUSA.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Previous studies using MHUSA in broilers showed that birds under this semiochemical had greater LW compared with control (Madec et al, 2005(Madec et al, , 2006(Madec et al, , 2008. The current study results are similar for LW, but the results did not support the hypothesis that CI would be improved for broilers exposed to MHUSA.…”
Section: Discussioncontrasting
confidence: 89%
“…Our treatment was identical to the one tested and described in the study by Madec et al (2006). Briefly, the treatment was incorporated into a gelatin matrix block composed of water (135 g), nonionic surfactant (7 g), and a gelling gum (5 g), plus either 3 g of water (control) or 3 g of MHUSA.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also known that hens raising their chicks produce specific hormonal secretions from this gland (Richard-Yris et al, 1983;Bohnet et al, 1991). Their lack may be related to the level of stress observed in broiler husbandries, as observed by Madec et al (2005) and Madec et al (2006). In order to test the effect on the quality of broilers' production, the secretion from the uropygial gland of hens was isolated under natural mothering conditions.…”
Section: Introductionmentioning
confidence: 99%